Perancangan Sistem Informasi Calon Wisudawan Universitas Advent Indonesia - Adam William Yordan Sihotang; Elmor Benedict Wagiu (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2020)
The use of a technology is currently very widely used in the community. The registration information system for prospective graduates is very important in the world of education, especially at Adventist University of Indonesia. With this system, it can help student when registering online graduate candidates by filling out the registration form online and opening it though the paper form that BAA has Provided. Information System for the registration of prospective graduates, utilizing hardware and software, as well as manual procedures such as providing document as condition for registering as prospective graduates. The use of platforms makes it easy to access the system anywhere by using devices connected to the network. But in this design, the system used is in the Adventist University network. With this system, BAA is very helpful in data processing for prospective graduate student.